Integrating TNF-α with Established Tumor Markers to Enhance Prognostic Accuracy in Gastric Cancer: A Prospective Observational Study - Mihai Catalin Rosu; Cristi Tarta; Silviu Moldovan; Andreea-Adriana Neamtu; Andrei Ardelean; Marco Capitanio; Diana Herczeg; Ionut-Flaviu Faur; Renata Bende; Luminita Pilat; Virgiliu Mihai Prunoiu; Carmen Neamtu; et al. (Biomedicines)
Background/Objectives: Gastric cancer remains a leading cause of cancer mortality worldwide. Reliable biomarkers are crucial for early detection, prognostication, and therapy monitoring. While classical tumor markers such as carcinoembryonic antigen (CEA), cancer antigen (CA)19-9, CA72-4, and alpha-fetoprotein (AFP) are used in clinical practice, their accuracy can be limited. Tumor necrosis factor alpha (TNF-α) is an inflammatory cytokine implicated in tumor progression, yet its relationship with established gastric cancer tumor markers has not been fully clarified. This study aimed to determine whether elevated TNF-α correlates with key tumor markers and disease stage in gastric cancer. Methods: In this prospective observational study, we enrolled 80 gastric cancer patients and 20 non-neoplastic controls. Baseline clinical data, laboratory parameters, and tumor markers (CEA, CA19-9, CA72-4, AFP) were recorded. TNF-α concentrations were measured using enzyme-linked immunosorbent assays. Correlation analyses and multivariate regression were performed to assess the relationship of TNF-α with tumor markers, inflammatory indices, and disease stage. Results: TNF-α was significantly elevated in gastric cancer patients (median 4.5 pg/mL) compared to controls (2.9 pg/mL). TNF-α showed a robust correlation with CA19-9 (rho = 0.502) and CA72-4 (rho = 0.385), and a moderate correlation with CEA (rho = 0.279). TNF-α concentrations were highest in Stage IV disease and in the intestinal-type histology. In regression analysis, only CA19-9 and CA72-4 remained independent predictors of TNF-α after controlling for clinical confounders. Conclusions: TNF-α is strongly associated with CA19-9 and CA72-4 and rises with advancing stage, highlighting its potential as an adjunct marker for assessing gastric cancer burden. These findings provide a rationale for further research on TNF-α as both a prognostic biomarker and a possible therapeutic target in gastric cancer.